Trends in access to health services, financial protection and satisfaction between 2010 and 2016: Has China achieved the goals of its health system reform?. (January 2020) - Ta, Yuqi; Zhu, Yishan; Fu, Hongqiao
Abstract: Guided by the principle of universal health coverage, China began its complex health system reform in 2009. Using data from the China Family Panel Studies (CFPS), this study assesses trends in healthcare utilization, financial protection, and satisfaction between 2010 and 2016. We use difference-in-means tests and regression analysis to evaluate overall trends and compare subsample results by urban/rural residence and income quartiles to examine changes in inequity. Our results show that China has achieved substantial improvements in access to healthcare services and financial protection since the health system reform in 2009. First, China has experienced a substantial increase in both inpatient and outpatient care utilization between 2010 and 2016. Second, people receive better financial protection by measures of health insurance coverage, inpatient reimbursement rate, the likelihood of incurring catastrophic health expenditure, and the likelihood of medical impoverishment. Third, inequity in financial protection by income quartiles has significantly decreased, though poorer groups remain more vulnerable. However, we do not observe a concurrent increase in satisfaction towards the health system. We also find that people are more willing to seek medical services in hospitals rather than primary care institutions. All these results suggest that China's ongoing health system reform should pay more attention to establishing a tiered health delivery system, strengthening financial protection for the poor, and increasing responsiveness to rising expectations. Highlights: China has achieved substantial improvements in access to healthcare services. From 2010 to 2016, people received better financial protection in healthcare. Inequity in financial protection by income quartiles has decreased. We do not observe a concurrent increase in satisfaction towards the health system.